Pemanfaatan Miang Bambu Betung (Dendrocalamusasper) Sebagai RacunTikus Utilization of “Miang”Dendrocalamus asper (bambu betung) as Rat Poison - Frans Hutasoit; Yunus Afifuddin; Ridwanti Batubara (Program studi Kehutanan USU, 2015)
The used chemically rodenticides to control rodent pest can have a negatively impact on the environment and human life. Utilization of eco-friendly natural materials such as “miang “ Dendrocalamus asper(bambu betung) is one kind of solution that is expected to be used as an alternative material to control rodent pest. This research purposed to determine the effectivenes of “miang” Dendrocalamus asper(Bambu Betung) against mortality of white rats (Rattus novergicus, L.) by used the baits mixed with bamboo miang betung at various concentrations (0%, 5%, 10%, 15%, 20%) on rodent morbidity and mortality rate . The results of this research indicates that mixing the bamboo miang into baits, effect on mortality of rodent. The concentration of 10% of the measure is the most effectivebecause has killed 100% of rats. This research indicates that miang bamboo high toxicity and very potential to be develope as an eco-friendly plant-based rodenticides. Keywords: Dendrocalamus asper,miang, rat, rodenticides, mortality